Snakes and ladders - Morpurgo, Michael; Wilson, Anne (New York, NY : Crabtree Pub. Co., 2000)
Because she is slender and cries at sad stories, Wendy is teased by the school bully until the day she brings in her grandfather's huge snake, then has to bravely rescue him after he wriggles out of her school bag.
Keywords: King snakes; Snakes as pets; Bullies; Schools; Grandfathers; Single-parent families